Prototype of a Two-Phase Axial-Gap Transverse Flux Generator Based on Reused Components and 3D Printing - Víctor Ballestín-Bernad; Jesús Sergio Artal-Sevil; José Antonio Domínguez-Navarro (Energies, 2023)
This paper presents a prototype of a low-cost two-phase axial-gap transverse flux generator, in which the magnetic and electric circuits have been made of reused materials, and the stator housing has been manufactured by 3D printing of plastic. Therefore, this work presents as a novelty the combination of the novel transverse flux topology and two challenging trends in electrical machines manufacturing, such as reusing of components and additive manufacturing. Axial-gap transverse flux machines potentially enable the combination of two of the main advantages of axial flux machines and transverse flux machines, i.e., short axial length and a high number of poles. The two-phase arrangement with shared air gap is of great interest in order to reduce further the axial length while avoiding the use of magnetic materials in the rotor, such as iron or soft magnetic composites. However, the equivalent air gap might be large, with significant leakage and fringing effects as the magnetic flux closes through the air. Therefore, in this paper the accuracy of the analytical equations and the magnetic equivalent circuit is firstly investigated. The two-phase axial-gap transverse flux machine is prone to misalignment between phases and rotor imbalances that alter the air gap length, so these effects have been included in the simulations with the finite element method. Experimental tests have been conducted throughout the investigation, from the prototype characterization to the steady-state operation, both with no load and with resistive loads.